Utilizing Proton Resonance Frequency of Isotopes Materials for Ultra-Precise Temperature Measurement: A Review - Abdullah, M.A. (EDP Sciences, 2017)
High energy management in nuclear system and refractory metals productions are equipped with challenging procedures in terms of precise and remote controlling. In order to predict occurrence of contamination and avoidance of huge damages, there are often difficulties to access the equipment during their operation. In addition, estimating the precise and remote nucleation critical temperature of decay and growth of radioactive materials in the nuclear system has also proven to be a great challenge. Other than that, the eutectic crystallization temperature of the refractory metals during production also need to provide a precise estimation. However, it has been understood that the conventional temperature sensors are yet to be applicable to work precisely in such harsh environments. On the other hand, proton resonance frequency thermometry phenomenon have not been utilized or developed to serve as temperature sensors; despite the fact that they are capable to measure temperature in quantum level. Therefore, this article provides a review of the prior art on proton resonance frequency thermometry with its application and reliability, and elaborates on the trajectory of ultra-precise temperature measurement as the latest development. © The authors, published by EDP Sciences, 2017.